Malaysian University Student Learning Involvement Scale (MUSLIS): Validation of a Student Engagement Model - Fauziah Md. Jaafar; Rosna Awang-Hashim; TENGKU FAEKAH TENGKU ARIFFIN (UUM Press, 2012)
Purpose - In western countries, a model to explain student engagement in college or university has long been established. However, there is a lack of research to develop and validate a model which may help to better understand student engagement in the local university context. There is currently no established instrument to measure student engagement specifically in the Malaysian (or Asian) university context. This study was conducted to fill the gap. A measurement model on student engagement in the Malaysian university context, based on Astin's (1984) Student Involvement Theory, was developed and validated for use in the local context.   Methodology - This study uses a survey research method to test the Malaysian University Student Learning Involvement Scale (MUSLIS), a measurement model of student engagement in the local university context. The MUSLIS is a 24-item scale designed to obtain feedback on the extent of student engagement at the tertiary level in the Malaysian context. The questionnaire was distributed to 347 final year students from Universiti Utara Malaysia. The data was analysed using the SPSS software (version 16.0) to run the exploratory factor analysis (EFA) and AMOS (version 16.0) to analyse the confirmatory factor analysis (CFA).   Findings - Holistic evaluation of the model of student engagement found that the data collected acceptably fit the model. The instrument used was also found to be reliable.   Significance - This study pioneers research in the measurement of tertiary student engagement, the first of its kind, in the Malaysian context. However, a wider sample comprising data from different universities in the country should be conducted to further confirm the usability and validity of the proposed MUSLIS. The instrument can be used in studies which seek to examine the outcomes of student involvement. In practice, the measurement of student involvement provides useful information on the extent of student participation in activities on and out of campus, whether these are academic-oriented or societal activities.